Examination of an analytical approach for load-displacement behavior of drag embedement anchors an their geometrical optimization - Dao, Duy Anh; Grabe, Jürgen; Chmelnizkij, Alexander (American Society of Mechanical Engineers, 2024)
Floating offshore renewables require anchorage to the seabed, often applying drag embedment anchors (DEAs). Industry standards use analytical solutions for evaluating DEA holding capacity and displacement behavior, but their complexity causes challenges in interpretation. This research provides a parametric and graphical analysis of a key analytical solution used internationally to predict the load-displacement behavior of DEAs in clay. It aims to clarify this solution’s calculations and identify optimal DEA geometry. Optimal shaft and fluke lengths for a simplified DEA are determined based on weight and cost-effectiveness (minimum volume) and safety (maximum bearing capacity and penetration depth). A solution set is presented, showing various optimal solutions tailored to predefined objectives. Comparative examination of ten DEA configurations reveals that no single design is universally optimal. Instead, strategic balancing of objectives, such as operational efficiency, cost-effectiveness, and safety margins, is essential. This approach underscores the need for a holistic view in DEA design, accommodating diverse objectives to achieve effective anchorage solutions. In conclusion, the study validates the applicability of established analytical solutions in predicting DEA behavior and in determining optimal geometries. These insights are crucial for economic efficiency and safety, offering guidance for future sustainable and reliable offshore infrastructure design.